KOMPYUTERNING QUVVAT SARFINI HISOBLASH TAMOYILLARI - Xolnazarov Fazliddin (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In this article, several explanations of the principles of calculating the power consumption of a computer are given, enriched with instructions for calculating the power consumption, as well as the reasons why calculating the power consumption of computers and using them in an energy efficient way can help reduce global energy consumption. Instructions are given on the importance of taking measures to use the computer in an energy-efficient manner, for every user and company.